2020
DOI: 10.1183/13993003.00918-2020
|View full text |Cite
|
Sign up to set email alerts
|

Accelerated FEV1decline and risk of cardiovascular disease and mortality in a primary care population of COPD patients

Abstract: Accelerated lung function decline has been associated with increased risk of cardiovascular disease (CVD) in a general population, but little is known about this association in chronic obstructive pulmonary disease (COPD). We investigated the association between accelerated lung function decline and CVD outcomes and mortality in a primary care COPD population.COPD patients without a history of CVD were identified in the Clinical Practice Research Datalink (CPRD-GOLD) primary care dataset (n=36 282). Accelerate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 36 publications
2
26
0
1
Order By: Relevance
“…Previous studies have investigated how patient characteristics are associated with FEV 1 decline; however, the purpose of this study was to primarily show how mean rates of FEV 1 decline differed depending on the definition used. [8][9][10]20,21 We found that in the cohorts that did not exclude measurements or individuals due to increases in FEV 1 , the mean rates of FEV 1 and within patient variation remained similar. For this reason, the definition used to create population one (i.e., using all available FEV 1 measurements over follow-up) could be used to describe the rate of FEV 1 decline in a COPD population using CPRD data.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…Previous studies have investigated how patient characteristics are associated with FEV 1 decline; however, the purpose of this study was to primarily show how mean rates of FEV 1 decline differed depending on the definition used. [8][9][10]20,21 We found that in the cohorts that did not exclude measurements or individuals due to increases in FEV 1 , the mean rates of FEV 1 and within patient variation remained similar. For this reason, the definition used to create population one (i.e., using all available FEV 1 measurements over follow-up) could be used to describe the rate of FEV 1 decline in a COPD population using CPRD data.…”
Section: Discussionmentioning
confidence: 65%
“…Whilst an FEV 1 measurement of 7 L would be considered high in COPD patients, a distribution of FEV 1 measurements was considered based off previous studies. [8][9][10] A previous validation study of spirometry in CPRD GOLD found that of 96.5% of spirometry traces recorded at the general practice in COPD patients were of adequate quality where a respiratory clinician was able to make an interpretation. 6 Of these, 27.9% were identified as post-bronchodilator FEV 1 , 7.2% were confirmed to be pre-bronchodilator FEV 1 , and for the remaining measurements it was unclear if the measurements were pre-or post-bronchodilator.…”
Section: Fev 1 Measurementsmentioning
confidence: 99%
“…While this algorithm would improve the certainty of including patients with COPD, rather than patients with asthma, for example, it does limit the comparability of findings with patients identified in the EGB data. Despite this, our previous work shows that only 7.3% of patients with a clinical diagnosis of COPD were never smokers in a CPRD GOLD COPD cohort in the UK and we believe that patients hospitalised for COPD or on long-term COPD therapy would have also been given a COPD diagnosis in primary care in France 22…”
Section: Discussionmentioning
confidence: 79%
“…A total of 5 included studies focused on the relationship between asthma and AF risk ( 16 , 20 22 ). Li et al ( 13 ) reported the race- and sex-specific association of asthma with AF incidence, separately.…”
Section: Resultsmentioning
confidence: 99%